Pelanggaran Maksim pada Tuturan Tokoh dalam Novel Kembara Rindu Karya Habiburrahman El Shirazy - Potabuga, Nur Atika; Masie, Sitti Rachmi; Kadir, Herson (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
This research is motivated by the problem of speech in the conversations of characters that do not comply with the principles of cooperation. The purpose of this study is to examine violations of the principles of cooperation in the speech of characters in the novel Kembara Rindu by Habiburrahman El Shirazy. Researchers used reading, listening, and note-taking methods, which were then analyzed using descriptive analysis techniques. The results showed that in the novel Kembara Rindu there were 31 conversation data that violated the principles of cooperation which included four maxims: violation of the maxim of quantity, violation of the maxim of quality, violation of the maxim of relevance, and violation of the maxim of manner/implementation. From the 31 data, 12 meanings of violations of the principles of cooperation were found.